2013
DOI: 10.1155/2013/236963
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin versus Nonabsorbable Disaccharides for the Treatment of Hepatic Encephalopathy: A Meta-Analysis

Abstract: Background. Many studies have found that the antibiotic rifaximin is effective for the treatment of hepatic encephalopathy. However, there is no uniform view on the efficacy and safety of rifaximin. Methods. We performed a meta-analysis through electronic searches to evaluate the efficacy and safety of rifaximin in comparison with nonabsorbable disaccharides. Results. A total of 8 randomized controlled trials including 407 patients were included. The efficacy of rifaximin was equivalent to nonabsorbable disacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 30 publications
2
33
3
2
Order By: Relevance
“…Our analysis showed that the treatment of RIF ranked first in reducing blood ammonia concentration among all interventions for patients with OHE. A traditional meta‐analysis in 2013 showed that patients in RIF group had lower serum ammonia levels vs. control group although this was not statistically significant. Consistent with this observation, our further pair‐wise meta‐analysis showed that RIF has a beneficial effect on HE and lowers serum ammonia with a mean difference of 7.10 lg/dL.…”
Section: Discussionmentioning
confidence: 98%
“…Our analysis showed that the treatment of RIF ranked first in reducing blood ammonia concentration among all interventions for patients with OHE. A traditional meta‐analysis in 2013 showed that patients in RIF group had lower serum ammonia levels vs. control group although this was not statistically significant. Consistent with this observation, our further pair‐wise meta‐analysis showed that RIF has a beneficial effect on HE and lowers serum ammonia with a mean difference of 7.10 lg/dL.…”
Section: Discussionmentioning
confidence: 98%
“…The searches were mainly conducted in MEDLINE/PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials [11,12] . The references cited in the included articles and relevant published reports were also searched manually.…”
Section: Search Strategymentioning
confidence: 99%
“…Rifaximin, a poorly absorbable oral antimicrobial drug, was first developed in Italy in 1985 and has been approved and was used widely in 68 countries including the USA and European countries at the end of 2015 . The indications for this drug are HE (covert HE and overt HE), idiopathic PSE, or hyperammonemic state in chronic liver diseases.…”
Section: Introductionmentioning
confidence: 99%